PENYULUHAN HUKUM PERSEROAN PERORANGAN DI KABUPATEN INDRAMAYU - Gunadi, Ariawan; Michelle, Grace Bernadette; Cendranita, Ivannia; Wonohadidjojo, Christopher Howard (Jurnal Serina Abdimas, 2023)
A Limited Liability Company ("PT") has a central function of the country's economy. Provisions related to this pt can be found in Law Number 40 of 2007 concerning Limited Liability Companies. The relationship between the Limited Liability Company Law and Law No. 11 of 2020 concerning Job Creation, regulates a new type of legal entity, namely Individual Companies, so that business entities incorporated today can be established by one person. However, there are still few people who understand the regulations related to the requirements and stages of establishing an Individual Company. Therefore, micro and small businesses that do not have permits or legalities arise that absorb 97% of the entire workforce. This hinders the progress of the country's national economy. Thus, individual companies should be the main concern, because there are many positive impacts that can be generated by the existence of licensed micro and small enterprises ("MSEs"), both for the people and the country. Perseroan Terbatas (“PT”) punya fungsi sentral perekonomian negara. Ketentuan terkait dengan PT ini dapat ditemukan dalam Undang-Undang Nomor 40 Tahun 2007 tentang Perseroan Terbatas. Keterkaitan antara Undang-Undang Perseroan Terbatas dengan Undang-Undang No. 11 Tahun 2020 tentang Cipta Kerja, mengatur mengenai jenis badan hukum baru, yakni Perseroan Perseorangan, sehingga badan usaha berbadan hukum pada masa kini dapat didirikan oleh satu orang. Namun, masih sedikit masyarakat yang memahami regulasi terkait persyaratan dan tahapan pendirian Perseroan Perseorangan. Maka dari itu, timbul usaha-usaha mikro dan kecil yang tidak memiliki izin atau legalitas yang menyerap 97% dari seluruh tenaga kerja. Hal tersebut menghambat kemajuan perekonomian nasional negara. Dengan demikian, perseroan perorangan seharusnya menjadi perhatian utama, karena banyak dampak positif yang dapat dihasilkan oleh eksistensi usaha-usaha mikro dan kecil (“UMK”) yang berizin, baik untuk rakyat dan negara.